1
$\begingroup$

Use Complex Integrals/ Residue to evaluate $\int_0^\infty \frac{dx}{(x+1)^3 + 1}$

I'm not sure how to do this integration. It looks like partial fractions but I'm unsure.

$\endgroup$
  • $\begingroup$ are u forced to use residue theorem? this integral is easier solved by other methods $\endgroup$ – tired Nov 26 '15 at 23:34
2
$\begingroup$

Generally, we can evaluate integrals of the form

$$\int_0^{\infty} dx \, f(x)$$

using a contour integral of the form

$$\oint_c dz \, f(z) \log{z} $$

As long as $f$ is sufficiently well-behaved at the origin and at infinity and in between, we have

$$-i 2 \pi \int_0^{\infty} dx \, f(x) = i 2 \pi \sum_k \operatorname*{Res}_{z=z_k} f(z) \log{z_k}$$

In this case

$$f(z) = \frac1{(1+z)^3+1}$$

so that, for $k \in \{0,1,2\}$:

$$z_k = -1 + e^{i (2 k+1) \pi/3} = -\left [1-\cos{(2 k+1) \frac{\pi}{3}}\right ] + i \sin{(2 k+1) \frac{\pi}{3}}$$

Thus,

$$\int_0^{\infty} \frac{dx}{(1+x)^3+1} = -\sum_{k=0}^2 \frac{\log{z_k}}{3 e^{i 2 (2 k+1) \pi/3}}$$

where

$$\begin{align}\log{z_k} &= \log{|z_k|} + i \arg{z_k} \\ &= \log{2 \left | \sin{(2 k+1) \frac{\pi}{6}} \right |} - i \arctan{\cot{(2 k+1) \frac{\pi}{6}}} \\ &= \log{2} - i \frac{\pi}{2} + \log{\sin{(2 k+1) \frac{\pi}{6}}} + i (2 k+1) \frac{\pi}{6}\end{align}$$

so that

$$\begin{align}\sum_{k=0}^2 \frac{\log{z_k}}{3 e^{i 2 (2 k+1) \pi/3}} &= -i \frac13 \frac{\pi}{3} e^{-i 2 \pi/3} + \frac13 \log{2} e^{-i 2 \pi} + i \frac13 \frac{\pi}{3} e^{i 2 \pi/3}\\ &= -\frac{2 \pi}{9} \sin{\frac{2 \pi}{3}} + \frac13 \log{2}\end{align}$$

Finally, we may conclude that

$$\int_0^{\infty} \frac{dx}{(1+x)^3+1} = \frac{\pi}{3 \sqrt{3}} - \frac13 \log{2} $$

This agrees with a numerical integral in Mathematica v 9.0.

$\endgroup$
1
$\begingroup$

We have $$I = \int_0^{\infty} \dfrac{dx}{(1+x)^3+1} = \int_1^{\infty} \dfrac{dx}{x^3+1} = \int_1^0 \dfrac{-dx/x^2}{1/x^3+1} = \int_0^1 \dfrac{xdx}{1+x^3}$$ Hence, $$I = \int_0^1\dfrac{x+1}{3(x^2-x+1)}dx - \int_0^1\dfrac{dx}{3(x+1)} = \dfrac{\pi}{3\sqrt{3}}-\dfrac{\log2}3$$

$\endgroup$
1
$\begingroup$

$$I=\int_{0}^{+\infty}\frac{dx}{(x+1)^3+1}=\int_{1}^{+\infty}\frac{dx}{x^3+1}=\int_{0}^{1}\frac{x}{1+x^3}\,dx $$ The roots of $1+x^3$ lie at $-1,\xi=\frac{1+i\sqrt{3}}{2},\bar{\xi}=\frac{1-i\sqrt{3}}{2}$ and they are simple. Since: $$ \text{Res}\left(\frac{x}{1+x^3},x=-1\right) = -\frac{1}{3}$$ the partial fraction decomposition of $\frac{x}{1+x^3}$ is given by: $$ \frac{x}{1+x^3} = -\frac{1}{3(x+1)}+\frac{1+x}{3(1-x+x^2)} $$ and: $$ I = \frac{1}{2}-\frac{1}{5}+\frac{1}{8}-\frac{1}{11}+\ldots = \color{red}{-\frac{\log(2)}{3}+\frac{\pi}{3\sqrt{3}}}.$$

$\endgroup$
  • $\begingroup$ Jack, no offense, but your previous answer was wrong and your correction was merely a change to the correct answer provided by others. I think you really should show correction to a step as well. For example, are you sure your partial fractions decomposition is correct? Hint: @Leg got it right. $\endgroup$ – Ron Gordon Nov 27 '15 at 10:44
  • $\begingroup$ @RonGordon: no offense took, but I simply forgot to divide by three, then fixed it wrong. The decomposition $$\frac{x}{1+x^3}=-\frac{1}{3(x+1)}+\frac{1+x}{3(1-x+x^2)}$$ is now correct. $\endgroup$ – Jack D'Aurizio Nov 27 '15 at 10:48
  • $\begingroup$ Jack, with you I figured it was something as trivial as that. $\endgroup$ – Ron Gordon Nov 27 '15 at 10:56
0
$\begingroup$

HINT:

$$\int\frac{1}{\left(x+1\right)^3+1}\space\text{d}x=$$


Substitute $u=x+1$ and $\text{d}u=\text{d}x$:


$$\int\frac{1}{u^3+1}\space\text{d}u=$$ $$\int\left(\frac{2-u}{3(u^2-u+1)}+\frac{1}{3(u+1)}\right)\space\text{d}u=$$ $$\frac{1}{3}\int\frac{2-u}{u^2-u+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$\frac{1}{3}\int\left(\frac{3}{2(u^2-u+1)}-\frac{2u-1}{2(u^2-u+1)}\right)\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{1}{6}\int\frac{2u-1}{u^2-u+1}\space\text{d}u+\frac{1}{2}\int\frac{1}{u^2-u+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$


Substitute $s=u^2-u+1$ and $\text{d}s=(2u-1)\space\text{d}u$:


$$-\frac{1}{6}\int\frac{1}{s}\space\text{d}s+\frac{1}{2}\int\frac{1}{u^2-u+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{\ln|s|}{6}+\frac{1}{2}\int\frac{1}{u^2-u+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{\ln|s|}{6}+\frac{1}{2}\int\frac{1}{\left(u-\frac{1}{2}\right)^2+\frac{3}{4}}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$


Substitute $p=u-\frac{1}{2}$ and $\text{d}p=\text{d}u$:


$$-\frac{\ln|s|}{6}+\frac{1}{2}\int\frac{1}{p^2+\frac{3}{4}}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{\ln|s|}{6}+\frac{1}{2}\int\frac{4}{\frac{4p^2}{3}+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{\ln|s|}{6}+\frac{2}{3}\int\frac{1}{\frac{4p^2}{3}+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$


Substitute $2=\frac{2p}{\sqrt{3}}$ and $\text{d}w=\frac{2}{\sqrt{3}}\space\text{d}p$:


$$-\frac{\ln|s|}{6}+\frac{1}{\sqrt{3}}\int\frac{1}{w^2+1}\space\text{d}u+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$ $$-\frac{\ln\left|s\right|}{6}+\frac{\arctan\left(w\right)}{\sqrt{3}}+\frac{1}{3}\int\frac{1}{u+1}\space\text{d}u=$$


Substitute $v=u+1$ and $\text{d}v=\text{d}u$:


$$-\frac{\ln\left|s\right|}{6}+\frac{\arctan\left(w\right)}{\sqrt{3}}+\frac{1}{3}\int\frac{1}{v}\space\text{d}v=$$ $$-\frac{\ln\left|s\right|}{6}+\frac{\arctan\left(w\right)}{\sqrt{3}}+\frac{\ln\left|v\right|}{3}+\text{C}=$$ $$-\frac{\ln\left|s\right|}{6}+\frac{\arctan\left(\frac{2p}{\sqrt{3}}\right)}{\sqrt{3}}+\frac{\ln\left|v\right|}{3}+\text{C}=$$ $$-\frac{\ln\left|s\right|}{6}+\frac{\arctan\left(\frac{2\left(u-\frac{1}{2}\right)}{\sqrt{3}}\right)}{\sqrt{3}}+\frac{\ln\left|v\right|}{3}+\text{C}=$$ $$-\frac{\ln\left|u^2-u+1\right|}{6}+\frac{\arctan\left(\frac{2\left(u-\frac{1}{2}\right)}{\sqrt{3}}\right)}{\sqrt{3}}+\frac{\ln\left|u+1\right|}{3}+\text{C}=$$ $$-\frac{\ln\left|(x+1)^2-(x+1)+1\right|}{6}+\frac{\arctan\left(\frac{2\left((x+1)-\frac{1}{2}\right)}{\sqrt{3}}\right)}{\sqrt{3}}+\frac{\ln\left|(x+1)+1\right|}{3}+\text{C}=$$

$$\frac{1}{6}\left(-\ln\left|x^2+x+1\right|+2\ln\left|x+2\right|+2\sqrt{3}\arctan\left(\frac{2x+1}{\sqrt{3}}\right)\right)+\text{C}$$


Now set your boundaries:

$$\lim_{n\to\infty}\left[\frac{1}{6}\left(-\ln\left|x^2+x+1\right|+2\ln\left|x+2\right|+2\sqrt{3}\arctan\left(\frac{2x+1}{\sqrt{3}}\right)\right)\right]_{0}^{n}=$$ $$\lim_{n\to\infty}\left(\frac{1}{18}\left(-3\ln|n^2+n+1|+6\ln|n+2|+6\sqrt{3}\arctan\left(\frac{2n+1}{\sqrt{3}}\right)-\pi\sqrt{3}-\ln(64)\right)\right)$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.